Carlo Ginzburg. When a historian coins a symbol (2020)
In this article, we intend to analyze the trajectory, contribution, results and the influence of the world-renowned historian, Carlo Ginzburg. His is a protracted investigation, which has not only influenced this area of knowledge, but also very distinct fields of the humanities, the sciences, and the arts. Carlo Ginzburg has been recognized and identified mainly due to two historiographic achievements: microhistory and The Cheese and the Worms. On the one hand, he is seen as the greatest representative of microhistory, a current of Italian origin which expanded mainly in the 1980s. On the other hand, this historian has been identified with one of his most successful works, that with the greatest impact: The Cheese and the Worms (1976). Ginzburg’s book is an individual reconstruction, with the name and surnames,of an ordinary individual, who belongs to the peasantry,  to a subordinate class. But Ginzburg’s investigation comes to a turning point in the late in the 80s. His new books have a thin connecting thread that links very diverse issues in an imaginative way, which, when put together, show common resonances.